Routing protocol based on energy aware in ad hoc networks - Shi ZHENG; Wei-qiang WU; Qin-yu ZHANG; Nai-tong ZHANG (Tongxin xuebao)
An energy-aware routing protocol (EARP) was presented to minimize the effect of limit energy supply of terminals in ad hoc network.In the novel protocol,different transmission paths based on service state of single node and energy consumption of the whole network could be chosen.When transmission path was broken,local maintaining strategy was evoked to reduce re-transmission of data packets and therefore route efficiency was improved.Moreover,node energy levels were introduced to avoid transmission link brake caused by energy exhaustion.Simulations were carried out on NS2 platform.The results show that,in the same simulation environment,comparing to other routing protocols,this routing protocol performs more effectively on balancing the traffic load,protecting low energy nodes and prolonging the network lifetime.